Ethical Leadership and Knowledge Hiding: A Moderated Mediation Model of Relational Social Capital, and Instrumental Thinking - Abdullah, Muhammad Ibrahim; Dechun, Huang; Ali, Moazzam; Usman, Muhammad (Frontiers in Psychology, 2019)
We examined the direct and indirect (via relational social capital) relationship between ethical leadership and knowledge hiding. We also tested the moderating role of instrumental thinking in the relationship between ethical leadership and knowledge hiding and the relationship between ethical leadership and relational social capital. Data were collected from 245 employees in different firms spanning different manufacturing and service sectors. The results showed that ethical leadership was negatively related to knowledge hiding, both directly and via relational social capital. The results revealed that instrumental thinking moderated the positive relationship between ethical leadership and relational social capital, such that the relationship was weak when instrumental thinking was high. The results also showed that instrumental thinking moderated both direct and indirect relationships between ethical leadership and knowledge hiding, such that the relationships were weak when instrumental thinking was high. The study carries important practical implications for managers concerned about the destructive consequences of knowledge hiding.